Method to Generate Electric Power and Hydrogen in the Absence Of External Energy - Ono, Katsutoshi (Journal of New Developments in Chemistry, 2018)
This paper describes the theoretical foundations for the electric power and hydrogen generator that functions with zero energy input without violating the laws of thermodynamics. This generation system is a combined energy cycle consisting of the H2O=H2+1/2O2 reduction reaction performed by the water electrolytic cell and the H2+1/2O2=H2O oxidation reaction performed by the fuel cell. This electrolytic method differs from the conventional electrolytic scheme in that if a quasi-static process is assumed, so that the theoretical power requirement is only 17% of the total energy required. This method performs electrostatic-to-chemical energy conversion by electrostatic-induction potential-superposed electrolytic scheme. If this electrolytic cell that delivers the pure stoichiometric H2-O2 mixture is combined with a fuel cell to form an energy cycle, then this may lead to the concepts of a hydrogen redox electric power generator and a hydrogen redox hydrogen generator that use alkaline water electrolyte or solid polymer electrolyte membrane (PEM) for both electrolytic cell and fuel cell. In the power generator, part of power delivered by the fuel cell is returned to the electrolytic cell, and the remainder represents the net power output. According to calculations based on data from the operational conditions for commercially available electrolytic cell and fuel cell, more than 70% of the power delivered from the fuel cell can be extracted outside the cycle as net power output without the use of any external source of energy.
Keywords: Electric power generator; Hydrogen generator; Water-electrolytic cell; Fuel cell